2022
DOI: 10.1049/ise2.12102
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of non‐profiled side channel attacks based on deep learning techniques

Abstract: In modern embedded systems, security issues including side-channel attacks (SCAs) are becoming of paramount importance since the embedded devices are ubiquitous in many categories of consumer electronics. Recently, deep learning (DL) has been introduced as a new promising approach for profiled and non-profiled SCAs. This paper proposes and evaluates the applications of different DL techniques including the Convolutional Neural Network and the multilayer perceptron models for non-profiled attacks on the AES-128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A technique for conducting sensitivity analysis known as gradient visualisation was used by Masure et al in order to locate the areas where information was being leaked [15]. Van der Valk and Picek improved upon bias-variance decomposition and introduced GE bias-variance decomposition [16] in…”
Section: International Journal Of Professional Studiesmentioning
confidence: 99%
“…A technique for conducting sensitivity analysis known as gradient visualisation was used by Masure et al in order to locate the areas where information was being leaked [15]. Van der Valk and Picek improved upon bias-variance decomposition and introduced GE bias-variance decomposition [16] in…”
Section: International Journal Of Professional Studiesmentioning
confidence: 99%
“…According to Martinasek et al [13], it was shown that MLP can crack naïve AES. In addition, R. Gilmore et.…”
Section: Review Of Workmentioning
confidence: 99%
“…Then, several works take into account different machine learning approaches to carry out tuning of hyperparameter by randomized or grid searching. The authors of [19] undertake an experimental assessment of various hyper-parameters concerning CNNs using ASCAD repository. To create deep learning model ensembles, Perin et al used a random search inside pre-specified ranges [20].…”
Section: Literature Reviewmentioning
confidence: 99%